Cryptographic hash function: a high level view - Taha, Imad; Alahmad, Mohammad A. (IGI Global, 2015)
Cryptographic hash function verifies data integrity and sender identity or source of information. The task is accomplished by taking a variable bit patterns as an input then produces a fixed bit patterns of output. This chapter provides a detailed overview to include classification, properties, constructions, attacks, applications and an overview of a selected dedicated cryptographic hash function.